PENGARUH SOSIAL MEDIA TERHADAP KARAKTER SIKAP MAHASISWA STMIK PALANGKA RAYA: The Influence of Social Media on the Character Attitudes of STMIK Palangka Raya Students - Zulkarnain, Dewanto; Sitohang, Hotmian; Rosmiati, Rosmiati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Mobile web is a browser that can be accessed using a smartphone or tablet device. This study aims to design an application for learning media, which can be used by students in lectures. In education, a guaranteed and quality learning process is needed in order to create appropriate learning. Learning Pancasila in higher education is a compulsory subject that must be taken by students. In Pancasila lessons, it is useful to study, analyze, and solve Pancasila as the ideology and basis of the Republic of Indonesia. One of the problems that arise is the unavailability of electronic learning media that is able to attract student interest in learning, so this course is less attractive. This research uses a prototype software development method which is carried out in 5 stages, namely: communication, planning, modeling, prototype formation, and submission of the system or system in testing. This research produces a learning media product for Pancasila courses. The learning media component contains digital book features and practice questions that are made in an interesting and interactive way.